Factors in javelin hrow that result in differences in throwing records between throwers with similar approach velocities - Takigawa, H.; Tauchi, K. (International Journal of Sport & Health Science, 2023)
The aim of this study was to determine the movement factors that cause differences in throwing records in javelin throwers who had similar running velocities. The movements of 81 female javelin throwers who participated in competitions were recorded using two cameras, and the coordinate values were obtained using the three-dimensional motion analysis technique. The preparatory phase was defined as the period from the last rear foot contact (RFC) to the fore foot contact (FFC), whereas the throwing phase was defined as the period from the FFC to javelin release. Among them, 14 athletes with approach velocity of 4.0-4.3 m/s at FFC were divided into a high (57.59 ± 3.60 m) and a low group (35.14 ± 8.23 m) for throwing records, and the kinematic data were compared. The high group had a significantly higher release velocity, showed larger maximum external rotation of the shoulder joint, and larger right shoulder velocity than the low group. Immediately during the throwing phase, the high group had a larger horizontal rotation of the upper trunk towards the throwing direction than the low group. Furthermore, the high group was characterized by greater height and segment length than the low group. These results indicate that the high group achieves larger terminal velocities owing to the faster rotation of the larger body. Thus, the results clearly show that high-performance athletes transfer greater kinetic energy to the javelin throw with a more rational throwing motion, even if they have a similar approach velocity.